Transcription Factor CREB3L1 Regulates Vasopressin Gene Expression in the Rat Hypothalamus - Greenwood, Mingkwan; Bordieri, Loredana; Greenwood, Michael P.; Melo, Mariana Rosso [UNESP]; Colombari, Debora S. A. [UNESP]; Colombari, Eduardo [UNESP]; Paton, Julian F. R.; Murphy, David (Soc Neuroscience, 2014)
Arginine vasopressin (AVP) is a neurohypophysial hormone regulating hydromineral homeostasis. Here we show that the mRNA encoding cAMP responsive element-binding protein-3 like-1 (CREB3L1), a transcription factor of the CREB/activating transcription factor (ATF) family, increases in expression in parallel with AVP expression in supraoptic nuclei (SONs) and paraventicular nuclei (PVNs) of dehydrated (DH) and salt-loaded (SL) rats, compared with euhydrated (EH) controls. In EH animals, CREB3L1 protein is expressed in glial cells, but only at a low level in SON and PVN neurons, whereas robust upregulation in AVP neurons accompanied DH and SL rats. Concomitantly, CREB3L1 is activated by cleavage, with the N-terminal domain translocating from the Golgi, via the cytosol, to the nucleus. We also show that CREB3L1 mRNA levels correlate with AVP transcription level in SONs and PVNs following sodium depletion, and as a consequence of diurnal rhythm in the suprachiasmatic nucleus. We tested the hypothesis that CREB3L1 activates AVP gene transcription. Both full-length and constitutively active forms of CREB3L1 (CREB3L1CA) induce the expression of rat AVP promoter-luciferase reporter constructs, whereas a dominant-negative mutant reduces expression. Rat AVP promoter deletion constructs revealed that CRE-like and G-box sequences in the region between -170 and -120 bp are important for CREB3L1 actions. Direct binding of CREB3L1 to the AVP promoter was shown by chromatin immunoprecipitation both in vitro and in the SON itself. Injection of a lentiviral vector expressing CREB3L1CA into rat SONs and PVNs resulted in increased AVP biosynthesis. We thus identify CREB3L1 as a regulator of AVP transcription in the rat hypothalamus.
Keywords: CREB3L1; hyperosmotic stress; hypothalamus; transcription; vasopressin